Representative Utterances In "Qomik Quran Juz 9" - Pratikayani, Arifah; , Drs. Agus Wijayanto M.A., Ph.D; , Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
The aim of this study is to describe the pragmalinguistics form and the illocutionary acts of representative utterances used in Qomik Quran Juz 9 comic by Edusarana 2005. This study uses descriptive qualitative method. The data were written text of representative utterance used in Qomik Quran Juz 9 by Edusarana 20115. The data of pragmalinguistics form were analyzed by Anna Trosborg and the illocutionary acts were analyzed by Austin's theory also added by Kreidler's theory as the types of representative utterances. The research findings showed that the pragmalinguistics form are downgraders: downtoners 5 data or 7,4%, understaters 1 datum or 1,5%, hedges 2 data or 2,9 %, subjectivizers 3 data or 4,4%, cajolers 4 data or 5,9%, and appealers 2 data or 2,9%; and upgraders: adjective intensifier 1 datum or 1,5 %, adverbial intensifier 21 data or 30,9%, commitment upgraders 23 data or 33,8%, lexical intensification 5 data or 7,4%, and do-instruction 1 datum or 1,5%. The intentions of them are based on the types of representative utterance, namely focus on information: announcing 6 data or 8,8%, declaring 10 data or 14,7%, disclosing 1 datum or 1,5% , explaining 12 data or 17,6%, expressing of boast 1 datum or 1,5%, expressing of getting angry 1 datum or 1,5%, expressing of need a help 1 datum or 1,5%, expressing of worry 1 datum or 1,5%, expressing of proud 1 datum or 1,5%, mentioning 6 data or 7,4%, proclaiming 2 data or 2,9%, relating 1 datum or 1,5%; focus on truth-value of utterance: affirming 8 data or 11,8% and asserting 3 data or 4,4%; focus on speaker's commitment/ involvement in what is reported: confiding 1 datum or 1,5% and professing 2 data or 2,9%; focus on manner of communicating: hinting 2 data or 2,9%, implying 2 data or 2,9%, and intimating 2 data or 2,9%; focus on the nature of message: dictating 1 datum or 1,5%; and focus on aspect: predicting 1 datum or 1,5% and recalling 3 data or 4,4%.